Armenia : Technical Assistance Report-Upgrading Fiscal Rules. (IMF Staff Country Reports; Country Report ;, 2017)
Armenia has made significant strides in enhancing macroeconomic stability over the past two decades. This has recently come under strain. Before a full recovery from the Global Financial Crisis (GFC) could take root, a second wave of external shocks, resulting from the slowdown in Russia and the ensuing sharp currency depreciation, buffeted the economy. Armenian public finances have deteriorated steadily since 2013, triggering the debt brake mechanism in 2016.